Current Status and Potential of Online Telemedicine in Plastic Surgery - Shunsuke Mima; Yoshiro Abe; Kazuhide Mineda; Yutaro Yamashita; Shinji Nagasaka; Hiroyuki Yamasaki; Mayu Bando; Makoto Mizuguchi; Kenta Ikushima; Teruyoshi Kageji; Ichiro Hashimoto (Journal of Plastic and Reconstructive Surgery)
Objectives: Remote medical care is becoming popular worldwide, but not as much has yet been done in plastic surgery. We provided online treatment related to plastic surgery using a 5G system. This study aimed to investigate the usefulness and future of online telemedicine in plastic surgery. Methods: A plastic surgeon alternated between face-to-face and telemedicine. The interval between consultations was 1 week. Specifically, local doctors and staff provided medical care to patients at the suburban hospital, and the plastic surgeon remotely observed patients and provided instructions and guidance on procedures to the local doctors and staff. In this study, we evaluated the patients who were treated under telemedicine with respect to their age, use, and effectiveness. The study encompassed the period from August 2021 to October 2022. Results: Thirty-five patients were treated via online telemedicine (mean age, 73.0 years). Twenty-one (60%) of the postoperative procedures were related to surgeries performed by a plastic surgeon. Consultation for simple wound care was performed in 8 (22.9%) patients. Guidance on pocket incision surgery for pressure ulcers was given to one patient. As for the quality of communication, images were clear, no delays were encountered, and no cases interfered with medical care. Conclusions: Our system was primarily useful as a postoperative management tool. The high image quality and low-latency communication allowed for real-time instruction during complex postoperative procedures and surgical techniques. Even in hospitals with infrequent visits from plastic surgeon, telemedicine has the potential to make surgery safer and more proactive.